2020
DOI: 10.18632/aging.103769
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin C intake with breast cancer risk and mortality: a meta-analysis of observational studies

Abstract: The association between vitamin C intake and breast cancer is unclear. This meta-analysis aimed to precisely assess the association of vitamin C intake with breast cancer risk and mortality. We searched the PubMed, Embase, and Web of Science databases up to June 2020 and found 69 studies relevant to breast cancer risk (54 studies) and survival (15 studies). Relative risks and 95% confidence intervals were calculated using the random-effects models. Pooled results suggested that the highest versus lowest vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 69 publications
1
21
1
Order By: Relevance
“…These data suggest that foods rich in vitamin C, such as cauliflower, kale, pineapple, sweet potato, bell peppers, peas, legumes, strawberries and citrus fruits should be part of the daily diet [ 4 , 225 ]. In a meta-analysis of numerous observational studies, vitamin C consumption was able to reduce breast cancer incidence by 11% when part of the daily diet, but a similar effect with vitamin C supplements was not [ 226 ]. More importantly, the study also showed that breast cancer recurrence remained lower in the higher vitamin C consumption group when compared with the lowest consumption group [ 226 ].…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that foods rich in vitamin C, such as cauliflower, kale, pineapple, sweet potato, bell peppers, peas, legumes, strawberries and citrus fruits should be part of the daily diet [ 4 , 225 ]. In a meta-analysis of numerous observational studies, vitamin C consumption was able to reduce breast cancer incidence by 11% when part of the daily diet, but a similar effect with vitamin C supplements was not [ 226 ]. More importantly, the study also showed that breast cancer recurrence remained lower in the higher vitamin C consumption group when compared with the lowest consumption group [ 226 ].…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…In a meta-analysis of numerous observational studies, vitamin C consumption was able to reduce breast cancer incidence by 11% when part of the daily diet, but a similar effect with vitamin C supplements was not [ 226 ]. More importantly, the study also showed that breast cancer recurrence remained lower in the higher vitamin C consumption group when compared with the lowest consumption group [ 226 ]. These observations have been confirmed in several other recent studies where vitamin C appears to enhance both radio- and immuno-therapy regimens, possibly through alterations in the neutrophil-macrophage ratio [ 227 , 228 , 229 , 230 ].…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…It is, therefore, clear that effect of vitamin C on incidence and progression of cancer in general is still a matter of controversy due to the complex disparities in the studies analyzed. [74] In relation to a meta-analysis performed on cancer types, we comment on three meta-analyses related to prostate cancer incidence. Stratton et al analyzed 14 studies, encompassing 4 randomized clinical trials, 8 cohort studies, and 2 case-control studies, which included a total of 265,932 subjects.…”
Section: Meta-analysis and Mendelian Randomization Studiesmentioning
confidence: 99%
“…Several of the studies were adjusted by body mass index, clinical characteristics of the tumor, and energy intake. In 2020, Zhang et al published a meta-analysis that included 69 studies and 17,067 women [ 74 ]. The results revealed no association between vitamin C intake and breast cancer risk (RR 0.85, 95% CI, 0.74–0.99), but there was significant association when only case-control studies were included (RR 0.74; 95% CI, 0.65–0.84; p < 0.001) and when dietary intake studies were included (RR 0.89; 95% CI, 0.82–0.96; p = 0.004) ( Table 2 ).…”
Section: Vitamin C In Cancer Prevention and Therapy—studies In Humansmentioning
confidence: 99%
“…In the estimation of highest VC intake vs. lowest, significant inverse associations were seen in VC intake and incidence of several cancers of the urogenital system: bladder cancer (source of VC intake: dietary, RR 0.84, 95% CI 0.73–0.98) ( 17 ), breast cancer (source of VC intake: dietary, RR 0.89, 95% CI 0.82–0.96) ( 18 ), endometrial cancer (source of VC intake: dietary, RR 0.85, 95% CI 0.73–0.98) ( 19 ), prostate cancer (source of VC intake: dietary, RR 0.89, 95% CI 0.83–0.94) ( 20 ), and renal cell carcinoma (source of VC intake: dietary, RR 0.78, 95% CI 0.69–0.87) ( 21 ). Additionally, VC was also related to decreased risk of breast cancer-specific mortality (source of VC intake: unknown, HR 0.78, 95% CI 0.69–0.88), breast cancer recurrence (source of VC intake: unknown, HR 0.81, 95% CI 0.67–0.99), and breast cancer all-cause mortality (source of VC intake: unknown, HR 0.82, 95% CI 0.74–0.91) ( 18 ). Nonsignificant association was detected in VC intake and risk of bladder cancer (supplementary intake/supplementary+dietary intake) ( 17 ) and breast cancer (supplementary intake) ( 18 ).…”
Section: Resultsmentioning
confidence: 99%